2012
DOI: 10.1021/es3022254
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Tertiary Wastewater Treatment Is Required for Water Resources Pollution Control in Africa

Abstract: T here is a significant lack of proper wastewater treatment in most African countries, especially in sub-Saharan Africa. Untreated sewage effluent is one of the most common types of pollution found around urban rivers and in groundwater sources in many African cities. By 2020, 75−250 million people in Africa may be exposed to increased water stress due to climate change and pollution will only exacerbate the situation. 1 In Kenya, for example, most municipal wastewater treatment plants (WWTPs) discharge partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Dudgeon, 2000). This is primarily because the majority of the industries do not have a proper treatment plant or plants have been kept idle to reduce operating costs (Omosa et al, 2012;Haque, 2017). Thus similar results can also be expected in other developing countries where wastewaters are being drained into the nearby water bodies without any prior treatment.…”
Section: Implications For Current Wastewater Management and Further Rmentioning
confidence: 74%
See 2 more Smart Citations
“…Dudgeon, 2000). This is primarily because the majority of the industries do not have a proper treatment plant or plants have been kept idle to reduce operating costs (Omosa et al, 2012;Haque, 2017). Thus similar results can also be expected in other developing countries where wastewaters are being drained into the nearby water bodies without any prior treatment.…”
Section: Implications For Current Wastewater Management and Further Rmentioning
confidence: 74%
“…The current management practice for wastes or industrial effluents in Bangladesh, as well as in other developing countries, is similar (e.g. Girija et al, 2007;Omosa et al, 2012;Haque, 2017) À draining them out into the nearby waters, usually rivers, usually without any prior treatment (e.g. Dudgeon, 2000).…”
Section: Implications For Current Wastewater Management and Further Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Stabilization ponds are widely used by industries including sugar, textile, dairy, and paper factories . Due to limited capability of stabilization ponds, the pollutant concentration in the effluent of pond system is still very high . For example, we found that the typical influent chemical oxygen demand of municipal WWTPs is often higher than 2000 mg/L in many pond systems in Africa, while it is approximately 400 mg/L in other countries .…”
Section: Sources Of Water Pollutionmentioning
confidence: 95%
“…This causes increase in water crisis and environmental deterioration (Bhatta R. et al, 2015 The increasing pace of urbanization and population growth continues to affect the quality of drinking water. The increasing consumption of water and discharge of wastewater has been resulted with the growing population and rising economy, which causes huge pollution (Omosa I. B. et al, 2012).…”
Section: Introductionmentioning
confidence: 99%